PENGARUH ACUPRESURE POINT FOR LACTATION TERHADAP PRODUKSI ASI IBU MENYUSUI - Fetrisia, Wiwit; Yanti, Yanti (Jurnal Kesehatan - STIKes Prima Nusantara, 2019)
Exclusive breastfeeding or more properly called exclusive breastfeeding. The reality in the field shows the production and ejection of breast milk is a bit of a constraint in breastfeeding. One solution to overcome the insufficiency of breast milk production is through techniques acupressure points for lactation. This study aimed to determine the effect of mother's milk production with acupressure point for lactation intervention in the work area of Muaro Paiti sub-district Kapur IX Lima Puluh Kota Regency 2018. A quasi-experimental design with control group pretest-posttest design. The study was conducted in the working area of Muaro Paiti Community Health Center in April 2018. The population was breastfeeding mother in the work area of Muaro Paiti health center which was 118 people, with purposive sampling of 16 people. Processing and data analysis is done computerized. Univariate results revealed the average production of breast milk before acupressure point for lactation intervention in breastfeeding mothers was 67,9 ml and after intervention 85.7 ml. Bivariate results have the effect of acupressure point for lactation intervention on maternal breastmilk production in the work area of Muaro Paiti District Health Center Kapur IX Lima Puluh Kota Regency Â 2018 (p = 0,0005). It is expected that health workers should be able to teach acupressure point for lactation techniques in breastfeeding mothers to increase milk production for mothers with breastfeeding production